Application of classical Hermitian self-orthogonal MDS codes to quantum MDS codes - Jin, Lingfei (2012)
In this paper, we first construct several classes of classical Hermitian self-orthogonal MDS codes. Through these classical codes, we are able to obtain various quantum MDS codes. It turns out that many of our quantum codes are new in the sense that the parameters of our quantum codes cannot be obtained from all previous constructions.